Family Planning in Islamic Perspectives - Suherman Suherman; Nur Romdhona; Noor Latifah; Triana Srisantyorini; Iswan Iswan (Indonesian Journal of Islam and Public Health, 2022)
Marriage has a broader and important scope, namely forming a happy family, physically and mentally prosperous (sakinah), harmonious, peaceful, prosperous, and most importantly to give birth to a new generation of quality for human survival. The government's step to make plans and restrictions as a balancer in a family is the Family Planning Program (KB) which has been included in the GBHN since 1973, implemented by all Indonesian people, with provisions for implementation on a voluntary basis and taking into account religious values. The Quran is the main source in Islamic teachings, related to family planning, in fact the Quran does not speak directly about family planning, but Islam only establishes an ethical framework for contemporary issues that arise. The hadith also explains that married couples should carefully consider household expenses while both are still alive, and lest their children become a burden to others, so that arrangements for the birth of children need to be considered together from the beginning of the marriage, for example by carrying out family planning program. Islam teaches the concept of a happy and prosperous family, as well as how to educate children and manage the family economy.